Dressed-state approach to a simple radiating atom - Flores-Hidalgo, G.; Malbouisson, APC (Elsevier B.V., 2005)
We consider a system consisting of an atom in the dipole approximation, coupled to the electromagnetic field. Using recently introduced renormalized coordinates and dressed states, we give a non-perturbative solution to the atom radiation process. From this formalism a non-exponential decay law naturally emerges. However, at least for low frequencies and weak coupling, there is only a very small, practically non-detectable, deviation from a purely exponential decay, in agreement with all previous results in the literature. (c) 2005 Elsevier B.V. All rights reserved.